Emotional Competencies and Entrepreneurial Intention: An Extension of the Theory of Planned Behavior - Verdesoto Velástegui, Oswaldo Santiago (2021)
This study analyzed the relationship between emotional competencies and entrepreneurial intention in final-year undergraduate students of public higher education institutions in Ecuador, supported by an extended model of Ajzen's Theory of planned behavior (1991). The results were derived from a questionnaire applied to students in the last semester of degrees involving academic business training. To analyze the results, structural equation modeling (SEM) was used. The findings show that emotional competencies are significant factors in the configuration of entrepreneurial intentions and have a direct and positive relationship with their cognitive precursors: entrepreneurial attitude and self-efficacy. It is suggested that students with a higher degree of emotional competencies cope better with the cognitive bias that can make it difficult to recognize business opportunities. The main contribution of this study was to generalize the results that have been obtained in the use of emotional competencies to promote the intentionality of entrepreneurship in the contexts of emerging economies.